ANALISIS RISIKO KESEHATAN LINGKUNGAN PAJANAN SULFUR DIOKSIDA PADA PEDAGANG DI TERMINAL SENEN TAHUN 2023 - Nanda Desi Rahma (2023)
Poor air quality in Jakarta due to dominance of motorized vehicles pollutant sulfur dioxide (SO2). SO2 can cause a risk health of humans and the environment to which they are exposed. This research using environmental health risk analysis methods to evaluate of traders due to SO2 exposure In real time and lifetime of SO2 exposure at Senen Terminal. This research was conducted on Monday from 11.00-13.00 WIB, using total approach sampling with 113 traders in Terminal Senen. SO2 measurements were carried out at 4 points connected with the existence of traders, namely the entrance, waiting room, kiosk, and exit. Measurement using turbidimetry and analyzed spectrophotometer as a calibrated SO2 meter officers from Balai K3 Jakarta as a third party. The results of this study showed the concentration of SO2 at Terminal Senen was 0.009 mg/m3, with the calculation of the intake value at traders in Senen Terminal, does not exceed the value RfC is 0.0013 and the calculation of the risk quotient value is still within safe limits. Based on the results obtained, it shows that no traders in Terminal Senen are at significant risk of consequence SO2 exposure both in real time and lifetime.